Pengaruh Kualitas Produk, Promosi, dan Persepsi Harga terhadap Tingkat Kepuasan Konsumen Mie Gacoan di Kutabumi Kabupaten Tangerang - Cerling Margareta Daeli; Agus Sriyanto (Jurnal Riset dan Inovasi Manajemen, 2025)
This study aims to examine the effect of product quality, promotion, and price perception on customer satisfaction at Mie Gacoan in Kutabumi, Tangerang Regency. The study population consists of consumers who have purchased Mie Gacoan, with a sample of 100 respondents selected using a non-probability sampling technique. Data was collected through questionnaires and analyzed using SPSS version 22. This study investigates the relationship between the independent variables (product quality, promotion, and price perception) and the dependent variable (customer satisfaction). The results of the analysis show that product quality, promotion, and price perception have a positive and significant effect on customer satisfaction at Mie Gacoan. High product quality, attractive promotions, and reasonable price perceptions contribute to increased customer satisfaction, which in turn can lead to greater loyalty and repurchase intentions. Based on these findings, it is recommended that Mie Gacoan management continuously improve their product quality and promotions, as well as maintain a favorable price perception among consumers. Enhancing these factors is expected to attract more customers and improve Mie Gacoan’s competitiveness in the market, particularly in the Kutabumi area and its surroundings. Therefore, this study provides valuable insights for marketing strategies and business development at Mie Gacoan, contributing to the growth and success of the brand in the competitive food service industry.